PERAN BPSK DALAM PENYELESAIAN SENGKETA KONSUMEN TRANSAKSI ELEKTRONIK BERDASARKAN UNDANG- UNDANG NOMOR 8 TAHUN 1999 - Haq, Miftahul (ANDREW Law Journal, 2024)
Electronic transactions are legal acts carried out using computers, computer networks, and/or electronic media. In electronic transactions, consumer losses can occur due to default or unlawful acts committed by business actors. Consumers also have the potential to be harmed if the products being traded are not registered with the government. The method used for research is called normative legal research. In order to resolve consumer disputes outside the courts, Law Number 8 of 1999 mandates the government to establish BPSK in districts/cities. BPSK decisions are final and binding. The execution of these decisions can be requested to the District Court. However, dispute resolution through BPSK does not eliminate criminal liability as regulated in Law Number 8 of 1999. BPSK decisions can be used as sufficient preliminary evidence for investigators to conduct investigations.